Posttranslational Modification of 6-Phosphofructo-1-Kinase in Aspergillus niger - Mesojednik, Suzana (American Society for Microbiology, 2005)
Two different enzymes exhibiting 6-phosphofructo-1-kinase (PFK1) activity were isolated from the mycelium of Aspergillus niger: the native enzyme with a molecular mass of 85 kDa, which corresponded to the calculated molecular mass of the deduced amino acid sequence of the A. niger pfkA gene, and a shorter protein of approximately 49 kDa. A fragment of identical size also was obtained in vitro by the proteolytic digestion of the partially purified native PFK1 with proteinase K. When PFK1 activity was measured during the proteolytic degradation of the native protein, it was found to be lost after 1 h of incubation, but it was reestablished after induction of phosphorylation by adding the catalytic subunit of cyclic AMP-dependent protein kinase to the system. By determining kinetic parameters, different ratios of activities measured at ATP concentrations of 0.1 and 1 mM were detected with fragmented PFK1, as with the native enzyme. Fructose-2,6-biphosphate significantly increased the V(max) of the fragmented protein, while it had virtually no effect on the native protein. The native enzyme could be purified only from the early stages of growth on a minimal medium, while the 49-kDa fragment appeared later and was activated at the time of a sudden change in the growth rate. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis of sequential purifications of PFK1 enzymes by affinity chromatography during the early stages of the fungal development suggested spontaneous posttranslational modification of the native PFK1 in A. niger cells, while from the kinetic parameters determined for both isolated forms it could be concluded that the fragmented enzyme might be more efficient under physiological conditions.